Community‐acquired pneumonia in immunocompromised older patients: incidence, causative organisms and outcome. (5th March 2012) - Sousa, D.; Justo, I.; Domínguez, A.; Manzur, A.; Izquierdo, C.; Ruiz, L.; Nebot, M.; Bayas, J.‐M.; Celorrio, J.‐M.; Varona, W.; Llinares, P.; Miguez, E.; et al.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect Abstract The number of elderly patients in the community with immunosuppressive conditions has increased progressively over recent decades. We sought to determine the incidence, causative organisms and outcome of community‐acquired pneumonia (CAP) occurring in immunocompromised older patients. We prospectively compared cases of CAP in immunocompromised and non‐immunocompromised patients admitted to five public hospitals in three Spanish regions. Of 320 cases studied, 115 (36%) occurred in immunocompromised patients, including: solid or hematological malignancy (97), corticosteroids or other immunosuppressive drugs (44), solid organ or stem cell transplant (five), and other conditions (eight). The etiology was established in 44% of immunocompromised patients vs. 32% of non‐immunocompromised patients (p 0.03). Streptococcus pneumoniae was the most common causative organism in both groups (29% vs. 21%; p 0.08), followed by Legionella pneumophila (3% vs. 6%; p 0.01). Gram‐negative bacilli were more frequent among immunocompromised patients (5% vs. 0.5%; p <0.01), particularly Pseudomonas aeruginosa (3% vs. 0%; p 0.04). Nocardiosis was only observed in immunocompromised patients (two cases). Bacteremia occurred similarly in the two groups. No significant differences were found with respect to ICU admission (8%, in both groups) or the length of stay (12.5 vs. 10.4 days). The early (<48 h) (3.5 vs. 0.5%; p 0.04) and overall case‐fatality rates (12% vs. 3%; p <0.01) were higher in immunocompromised patients. In conclusion, a substantial number of older patients hospitalized for CAP are immunocompromised. Although relatively uncommon, CAP due to gram‐negative bacilli, including P. aeruginosa, is more frequent among these patients. CAP occurring in immunocompromised patients causes significant morbidity and mortality.